2023
DOI: 10.1080/02103702.2023.2243781
|View full text |Cite
|
Sign up to set email alerts
|

Teaching-learning dynamics between schools and tutoring centres in India: a virtuous or vicious cycle? (Las dinámicas de enseñanza-aprendizaje en los centros escolares y los centros de tutorías privadas en la India: ¿ciclo virtuoso o ciclo vicioso?)

Shalini Bhorkar

Abstract: Unpacking the linkages between mainstream education and private tutoring is fundamental for advancing knowledge on tutoring's implications for learners and systems of learning. This paper explores the micro-processes of teaching-learning at schools and tutoring centres to provide a nuanced understanding of the dynamics between them, in the context of India. Using qualitative data from lesson observations, interviews and focus group discussions with 85 participants, the paper explicates the teaching-learning pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 47 publications
0
3
0
3
Order By: Relevance
“…It provides a comprehensive overview of international research on shadow education in the last three decades, introducing the main ideas behind the concept of shadow education and outlining the development of the field for the readers of JSED (Bray, 2023). The following four articles provide new empirical evidence on central issues within this special issue’s thematic focus, from the perspectives of four Asian societies: South Korea (Byun et al, 2023), Mainland China (Kwok & Wang, 2023), Hong Kong (Tsaloukidis & Kobakhidze, 2023) and India (Bhorkar, 2023).…”
Section: Special Issue On Shadow Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…It provides a comprehensive overview of international research on shadow education in the last three decades, introducing the main ideas behind the concept of shadow education and outlining the development of the field for the readers of JSED (Bray, 2023). The following four articles provide new empirical evidence on central issues within this special issue’s thematic focus, from the perspectives of four Asian societies: South Korea (Byun et al, 2023), Mainland China (Kwok & Wang, 2023), Hong Kong (Tsaloukidis & Kobakhidze, 2023) and India (Bhorkar, 2023).…”
Section: Special Issue On Shadow Educationmentioning
confidence: 99%
“…She found that the interacting dynamics are likely to implicate both learners and systems of learning. This includes the confusing and conflicting teaching and learning content from the two different educational contexts, and the overemphasis on curriculum and examinations in private tutoring within the broader mainstream education discourse that highlights students’ all-round development (Bhorkar, 2023).…”
Section: Special Issue On Shadow Educationmentioning
confidence: 99%
See 3 more Smart Citations